Religious Upbringing of Economic Migrants' Children: a Challenge for Parents, Priests and Catechists as Studied in Scotland - Tomasz Biernat; Piotr Krakowiak; Tomasz Leszniewski; Dagmara Turowska (Nicolaus Copernicus University in Toruń, 2018)
The aim of the article was to provide a description of the conditions affecting religious upbringing of children in families that are staying in Scotland during an economic migration. The perspective used encompasses the family environment, the parish, the Scottish educational system and its constituent catholic schools, and a Polish Saturday school. The presented research was conducted among Poles staying in Scotland. It shows that family emigration makes religious upbringing of children harder. We may attribute this to the following main factors: a weakening of the parents' religiosity, a lack of religious education in public schools, insufficient knowledge of catholic education, a limit of the capability of attending Polish language catholic mass, and a lay environment in which the children operate. A certain challenge for the emigrants is understanding the different character of catholic education in Scotland from that in Poland. A large problem is insufficient catechism activities which are usually ad hoc, limited in duration, and reach only a part of the children and youth. In families with weak religiosity, an emigration threatens the realization of the religious education and upbringing function of families and favors the cessation of faith. Pastoral and catechist activities with a large engagement of lay catechists are an attempt to deal with the challenges that families face with children being raised in dual language environments and cultures of varied attitudes to religious and spiritual needs.